2020
DOI: 10.1007/s10096-020-03992-8
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus agalactiae in pregnant women: serotype and antimicrobial susceptibility patterns over five years in Eastern Sicily (Italy)

Abstract: Streptococcus agalactiae (also known Group B Streptococcus or GBS) represents the main pathogen responsible for early- and late-onset infections in newborns. The present study aimed to determine the antimicrobial susceptibility pattern and the capsular serotypes of GBS isolated in Eastern Sicily over 5 years, from January 2015 to December 2019. A total of 3494 GBS were isolated from vaginal swabs of pregnant women (37–39 weeks), as recommended by the Centers for Disease Control and Prevention. Capsular polysac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 61 publications
0
31
0
7
Order By: Relevance
“…Macrolide-lincosamide-streptogramin B (MLS B ) phenotypes were determined by the double-disk diffusion test on MHA, as previously described [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…Macrolide-lincosamide-streptogramin B (MLS B ) phenotypes were determined by the double-disk diffusion test on MHA, as previously described [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similar to other reports (21,23), none of the isolates resistant to penicillin, ampicillin, and vancomycin was found in this study. Although the GBS resistance to ampicillin, penicillin, and vancomycin has been documented (22,24,25), penicillin and ampicillin remain the drugs of choice for intrapartum antibiotic prophylaxis for GBS colonization in Vietnamese pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…The high resistance rates described by us prohibits empirical use of these antibiotics for women with penicillin allergy. The increasing reports regarding penicillin resistance [ 12 , 13 ] warrant also routine susceptibility test for penicillin.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data reports increasing rates of macrolide resistance [ 10 , 11 ]. Also, several recent studies demonstrated a worrying increase in GBS isolates with resistance to penicillin [ 12 , 13 ]. In Israel, screening does not include antibiotic susceptibility and there is no data regarding GBS resistance rates.…”
Section: Introductionmentioning
confidence: 99%